#MeToo: Before and After. Issue 4 (2nd October 2018) - Pellegrini, Ann
ABSTRACT: This essay asks, why now? What contributed to the rapid public success of #MeToo in this contemporary moment? It situates the explosion of #MeToo within both a longer history of feminist debates and activism around sexual violence, in which feminists of color have played a leading role, and the rage and bewilderment so many women have experienced in the wake of Donald Trump's election. The author proposes the term "facilitative displacement" as a way to understand how Trump's election, despite and perhaps because of his known record of misogynist statements and assaultive behavior, may have fueled #MeToo.